2010
DOI: 10.1016/j.tem.2009.12.005
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1, oxidative stress and atheroprotection

Abstract: Atherosclerosis is a chronic inflammatory disease in which early endothelial dysfunction and subintimal modified lipoprotein deposition progress to complex, advanced lesions that are predisposed to erosion, rupture and thrombosis. Oxidative stress plays a critical role not only in initial lesion formation but also in lesion progression and destabilization. While growth factors are thought to promote vascular smooth muscle cell proliferation and migration, thereby increasing neointima, recent animal studies ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 148 publications
(138 reference statements)
2
88
0
1
Order By: Relevance
“…IGF-1 enhances NO production by increasing endothelial NO synthase. IGF-1 also upregulates anti-oxidant enzymes [29]. Additionally, Thum T et al [30] reported that IGF-1 in response to GH administrarion elevated circulating endothelial progenitor cell levels associated with increased NO bioavailability, thereby preventing endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 enhances NO production by increasing endothelial NO synthase. IGF-1 also upregulates anti-oxidant enzymes [29]. Additionally, Thum T et al [30] reported that IGF-1 in response to GH administrarion elevated circulating endothelial progenitor cell levels associated with increased NO bioavailability, thereby preventing endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…GH-deficient patients with low IGF1 levels had impaired flow-mediated arterial dilation, which was endothelium dependent and NO mediated (Higashi et al 2010). In untreated hypertensive adults, low plasma IGF1 levels were associated with reduced endothelial function as measured by acetylcholine (ACh)-stimulated forearm blood flow; by contrast, there was no correlation with endothelium-independent, sodium nitroprusside-induced vasodilation (Perticone et al 2008).…”
Section: Igf Actions In Endothelial Cellsmentioning
confidence: 99%
“…27 GH and IGF-1 have also been shown to have antioxidant and anti-inflammatory effects in animal models, suggesting a protective role for GH/ IGF-1 in vascular disease given the role of oxidative stress in initiating lipid-lesion formation as well as in the destabilization and progression of these lesions. 36 Interestingly, our data link IGF-1 levels to hyperlipidemia, highlighting a potential interplay between serum lipids and GH/IGF-1 levels. Although it is tempting to hypothesize that this correlation may indicate a response by the GH axis to hyperlipidemia, additional analysis is necessary to fully elucidate this.…”
Section: Discussionmentioning
confidence: 69%